Validitas Petunjuk Praktikum Berbasis POE (Predict, Observe, and Explain) - Sahratullah, Sahratullah; Seprianingsih, Dewi; Mardiana, Mardiana (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This research was carried out with the aim of finding out the validity of POE-based practicum instructions (Predict, Observe and Expline) at SMP Negeri 4 Taliwang. This type of research refers to the 4D development model, which consists of four stages, namely Define, Design, Develop, and Disseminate. This research stage was only carried out until the develop stage, namely testing development on a limited scale. This is because the POE (Predict, Observe and Expline) based practicum instructions have not yet reached the Disseminate stage, namely the dissemination stage at the high school level in West Sumbawa Regency. The instrument used in this research was a validation test sheet for POE-based practicum instructions with data collection techniques using the average expert validation score. The results of data analysis show that the development of a POE-based practical manual is valid and very suitable for use. The validation results obtained very high feasibility from the 10 assessment indicators with a value of 87.5%. POE-based practical instructions have been validated by a team of experts, then revised based on suggestions from the validator. As well as the results of the POE-based practicum instructions readability test on 15 indicators with easy criteria with a score of 98.64%. Among the 15 readability test indicators, there were 2 indicators that received hesitant answers from respondents and 3 indicators that received disagreeing answers from respondents. The implications of these practical instructions can be utilized by educators and students in learning in the classroom and outside the classroom, especially in laboratory activities.